Influence of Employee Age, Sex, and Job Status on Managerial Recommendations for Retirement - Rosen, Benson; Jerdee, Thomas H. (Academy of Management Journal, 1979)
This article presents information on a study which examines the effects of employee age, sex, and job status on managerial assessments toward the desirability of initiating retirement procedures for older workers. It infers that a content analysis of written justifications is important in identifying the influence of employee age on managerial judgments and to the understanding of the processes underlying these judgments. It suggests that the level of ambiguity surrounding retirement decisions demands better job analysis, job design and performance appraisal systems.